AN INTRODUCTION TO DIFFERENT TYPES OF GAS CHROMATOGRAPHY - Natasya Teonata; Vania Aurellia Wijaya; Vinkannola Sangdyah Vitaloka; Muhammad Thariq Attamimi; Muliasari Kartikawati (Program Studi Kimia, Universitas Lambung Mangkurat, 2021)
Gas Chromatography was first introduced traditionally by James and Martin on 1952. As years went on, gas chromatography was further developed by combining it with other instruments which acts as a detector. In this journal, 5 differents types of Gas Chromatography was discussed. Gas Chromatography Mass Spectrometry (GS-MS), Gas Chromatography-Olfactometry (GC-O), Gas Chromatography-Flame Ionization (GC-FID), Gas Chromatography-Time-of-Flight (GC-TOF) and Multidimensional Gas Chromatography (MDGC). Each type of Gas Chromatography is unique and utilized differently since differs in its detector at the end. The detector is responsible to send electrical signals to the computer to identify the gas that were tested.